ABOUT REMOTE TEACHING OF HIGHER MATHEMATICS IN QUARANTINE CONDITIONS - Hryshko, Olena Mykolaivna; Hural, Viktoriia Anatoliivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
This article describes specifics of teaching Further Mathematics after switching to distance education. The authors highlight both benefits and challenges arising when building a distance education process.